Effect of Degree of Smoking Based on Brinkman Index on Hemoglobin Levels in Adults - Wijaya, Bryan Anna; Sari Mariyati Dewi Nataprawira (Community Medicine and Education Journal, 2024)
Cigarette consumption is the main cause of death in the world because it affects various physiological conditions in the body. Various ingredients in cigarette smoke such as tar, nicotine, carbon monoxide, and others can cause health problems, especially in the O2 transportation system. Hemoglobin is a protein in red blood cells that carries oxygen from the lungs to all tissues. The carbon monoxide contained in cigarette smoke is competitive with O2 in binding to hemoglobin so that the oxygen distributed to the tissues is reduced. The body will compensate for peripheral hypoxia that occurs by increasing hemoglobin levels in the body so that oxygen transport to the tissues can be maintained. Research regarding the relationship between the degree of smoking and hemoglobin levels is still controversial. Analytical research with cross-sectional design. A total of 184 respondents were taken using purposive sampling and it was found that the majority (94%) were men who worked as security officers, cleaners, parking attendants, or technicians. Based on the Brinkman Index, 73.9% of respondents were classified as light smokers, only 1.6% were classified as heavy smokers and 50.5% of respondents had low hemoglobin levels. Analysis showed that the majority of respondents in the light smoker group had normal hemoglobin levels (58.1%), while moderate and heavy smokers had lower hemoglobin levels. In statistical analysis, a significant p-value (0.001) was found between the degree of smoking and hemoglobin levels.